Reconsidered Concept of «Prebiotics» and Their Impact on the Child's Organism - Olga L. Lukoyanova; Tatyana E. Borovik; Aleksandra V. Surzhik ("Paediatrician" Publishers LLC, 2018)
Detection of a large number of oligosaccharides in breast milk predetermined their use in the composition of infant formula. The most studied prebiotic simulating the unique properties of breast milk oligosaccharides is the scGOS/lcFOS mixture. Its efficacy is confirmed in clinical studies. In 2017, the experts of the  International Scientific Association of Probiotics and Prebiotics  (ISAPP) adopted a new definition for «prebiotics», which greatly  expanded the concept of their application. The World Allergy  Organization (WAO) recommends the use of prebiotics in allergy- prone children. The guidelines are based on the results of studies of the influence of prebiotics on the intestinal microbi, a violation of the composition and functions of which predisposes to the  development of allergy. Currently, the search for more promising  technologies for the production of prebiotics continues.